2004
DOI: 10.1890/02-4101
|View full text |Cite
|
Sign up to set email alerts
|

Population Demographics in Species With Biphasic Life Cycles

Abstract: Abstract. We develop and test models for the population dynamics of species that undergo regular alternations of generations between independent, free-living, haploid and diploid phases. The models are patterned after the dioecious, haploid-diploid lifecycle of many marine algae. If the two phases have equal demographic rates, all models (with or without density dependence) predict a stable distribution with a ratio of :1 (ϳ60% ͙2 haploids and 40% diploids). We find that observable deviations from this distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 52 publications
4
115
1
1
Order By: Relevance
“…Dissimilarities between ploidy phases were found over the fecundity rates by Santos and Duarte [20], Scrosati et al [24], Thornber and Gaines [29] and Thornber et al [30]. These could be seasonal, herbivory dependent and could possibly be due to their different cytological processes of gamete/spore production.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Dissimilarities between ploidy phases were found over the fecundity rates by Santos and Duarte [20], Scrosati et al [24], Thornber and Gaines [29] and Thornber et al [30]. These could be seasonal, herbivory dependent and could possibly be due to their different cytological processes of gamete/spore production.…”
Section: Discussionmentioning
confidence: 91%
“…Then, the ramets in Vandenberg should survive more, attain bigger sizes or get sexually mature later relative to those in Piedras Blancas. Thornber and Gaines [29] showed that a higher diploid fecundity was driving the average haploid dominance in Mazzaella flaccida, while their H:D spatial variability could only be explained by differences in mortality rates. Accordingly, Vieira and Santos [34] suggested that only through ploidy dissimilarities in survival may conditional differentiation drive an effective spatial niche partition.…”
Section: Discussionmentioning
confidence: 99%
“…For G. vermiculophylla, Rueness (2005) described a higher abundance of vegetative individuals in European waters. The different latitudinal, biological and physical processes might explain these differences (Thornber & Gaines, 2004). The patches we investigated in the Ria de Aveiro exhibited high variation in reproductive status, with some being almost always vegetative and others having a predominance of carposporophytic individuals.…”
Section: Field Studiesmentioning
confidence: 93%
“…Analysis of variance (ANOVA) is presented in Table 2. phase dominance in most Gigartinales species and that of G. skottsbergii population in South America (Piriz 1996;Avila et al 1999;Faugeron et al 2004). Phase dominance of specific macroalgal life stage may result from differences in spore production between generations (Scrosati & De Wreede 1999;Thornber & Gaines 2004) or fertilization rate (Fierst et al 2005). In the triphasic life history of red macroalgae, the carposporophyte phase represents an adaptation to minimize the effect of both low and variable fertilization rates, where the cloning of the zygote amplifies the production ratio of carpospores relative to tetraspores (Searles 1980).…”
mentioning
confidence: 99%